How does public perception of antibiotic use on dairy farms contribute to self‐reported purchasing of organic?. Issue 5 (6th May 2021) - Bulut, Ece; Stout, Alison; Wemette, Michelle; Llanos‐Soto, Sebastián; Schell, Robert C.; Greiner Safi, Amelia; Shapiro, Michael A.; Moroni, Paolo; Ivanek, Renata
Abstract : The United States regulates the use of antibiotics in agricultural settings to address the global antibiotic resistance problem. Conventional dairy cows treated with antibiotics are kept in the herd and after the withholding period milk is harvested. On organic farms, the US organic standard on antibiotic use requires sick dairy cows to be treated, but treated cows must be removed from the herd and their milk can never again be sold as certified organic. This study investigated the US public's perceptions of the organic dairy farming, antibiotic use on dairy farms, and whether these perceptions affect consumer's self‐reported purchasing behavior for organic. We used a nationally representative phone‐based survey of 1000 US adults and characterized participants' self‐reported (i) knowledge of the legality of antibiotic use on dairy farms (conventional and organic) and (ii) frequency of purchasing organic instead of conventional dairy products, as well as several demographic and other variables. The results indicated that participants' knowledge about antibiotic use practices in dairy farming have no effect on their self‐reported purchasing behavior for organic or conventional dairy products. However, respondents who were familiar with the regulations of antibiotic use on dairy farms were more likely to oppose the US organic standard on antibiotic use in dairy farming and thought that past antibiotic use should not permanently remove a cow's organic status. These findings contribute to understanding of public perceptions that shape the US dairy organic market. Practical Application: Income, employment, health and political values, but not consumers' knowledge about antibiotic use in dairy farming, affect self‐reported purchasing behavior for organic dairy products. However, consumers who are familiar with the regulations of antibiotic use on US dairy farms disagree with the US organic standard on antibiotic use mandating loss of organic status for any cattle treated with antibiotics. These findings may be useful to organic markets.